Anaerobic transcription activation in Bacillus subtilis: identification of distinct FNR-dependent and -independent regulatory mechanisms. - Cruz Ramos, H (EMBO J, 1995)
Bacillus subtilis is able to grow anaerobically using alternative electron acceptors, including nitrate or fumarate. We characterized an operon encoding the dissimilatory nitrate reductase subunits homologous to the Escherichia coli narGHJI operon and the narK gene encoding a protein with nitrite extrusion activity. Downstream from narK and co-transcribed with it a gene (fnr) encoding a protein homologous to E.coli FNR was found. Disruption of fnr abolished both nitrate and fumarate utilization as electron acceptors and anaerobic induction of narK. Four putative FNR binding sites were found in B.subtilis sequences. The consensus sequence, centred at position -41.5, is identical to the consensus for the DNA site for E.coli CAP. Bs-FNR contained a four cysteine residue cluster at its C-terminal end. This is in contrast to Ec-FNR, where a similar cluster is present at the N-terminal end. It is possible that oxygen modulates the activity of both activators by a similar mechanism involving iron. Unlike in E.coli, where fnr expression is weakly repressed by anaerobiosis, fnr gene expression in B.subtilis is strongly activated by anaerobiosis. We have identified in the narK-fnr intergenic region a promotor activated by anaerobiosis independently of FNR. Thus induction of genes involved in anaerobic respiration requires in B.subtilis at least two levels of regulation: activation of fnr transcription and activation of FNR to induce transcription of FNR-dependent promoters. IMAGES: